The Effect Of Heating On Antimicrobial Activity Of Gulai Seasoning - Winiati Pudji Rahayu; Dyah Sista Raharjanti (Jurnal Teknologi dan Industri Pangan, 2000)
The effect of heating on Gulai seasoning on its antimicrobial activity in food system, was evaluated against Staphylococcus aureus and Bacillus cereus. Food system used as growth medium was meat extract and coconut milk (1:1, v/v) and heat treatment applied to this study were stirfrying, boiling and sterilization. The analysis of antimicrobial activity using contact method showed that the inhibition of microbial growth was better in food system with seasoning than that without seasoning. Fresh Gulai seasoning was efective to inhibit total microbe and B. cereus for up to 6 and 24 hour, respectively. After stirfrying,Gulai seasoning inhibited total microbe and B. cereus 6 hours of incubation time. Increasing in time and temperature of heat treatment, resulted in the decrease of antimicrobial activity to total microbe and B. cereus . On the other hand, heat treatment of Gulai seasoning increased antimicrobial activity against S. aureus and the highest antimicrobial activity was reached by boiling Gulai stir-fried seasoning for 20 minutes.